1977
DOI: 10.1210/jcem-45-6-1220
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antigens and Antibodies in the Diagnosis of Thyroid Cancer

Abstract: Anti-thyroglobulin antibodies, anti-thyroid microsomal antibodies, serum thyroglobulin, and carcinoembryonic antigen were assayed in sera of patients with a history of thyroid irradiation and in patients with thyroid cancer. In irradiated patients, the frequency of positive results for each test was increased above the frequency found in a control population, with a significant increase at P less than .05 for TGHA and TG levels. However, the tests (with the exception of serum thyroglobulin) did not clearly seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…In agreement with previous studies carried Out using passive hemagglutination (DeGroot et al 1976;Mariotti et al 1978), microso¬ mal antibodies were more frequently found (23%) than thyroglobulin antibodies (7.5%). The inci¬ dence of thyroglobulin antibodies is lower than that reported in some recent studies (Feldt-Ras¬ mussen et al 1983;Ericsson et al 1985;Reiners & Hufner 1987;Hpier-Madsen et al 1984) per¬ formed using radioimmunoassays or ELISA tech¬ niques for antibody detection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous studies carried Out using passive hemagglutination (DeGroot et al 1976;Mariotti et al 1978), microso¬ mal antibodies were more frequently found (23%) than thyroglobulin antibodies (7.5%). The inci¬ dence of thyroglobulin antibodies is lower than that reported in some recent studies (Feldt-Ras¬ mussen et al 1983;Ericsson et al 1985;Reiners & Hufner 1987;Hpier-Madsen et al 1984) per¬ formed using radioimmunoassays or ELISA tech¬ niques for antibody detection.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of thyroglobulin antibodies by pas¬ sive hemagglutination has generally been found slightly increased when compared with that ob¬ served in healthy controls, with percentages rang¬ ing between 2.3 (Pinchera et al 1977) and 15% (Kornstad 1974;Amino et al 1975;DeGroot et al 1976 More scanty data are available for microsomal antibodies. No significant increase in microsomal antibodies was found by Kornstad (1974) in a large series of thyroid cancer using the rather insensitive complement fixation test, whereas a higher incidence (13%) of this type of antibody was reported by Amino et al (1975) using the indirect immunofluorescence technique, and by others (DeGroot et al 1976;Mariotti et al 1978) using passive hemagglutination, with percentage ranging between 13-21. All these studies, except the one by Kornstad were carried out in a small number of patients and no follow-up data were provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we assessed the association between the presence of thyroid antibodies and final outcome, we detected significantly higher rates of malignancy (P ϭ 0.02) in those with detectable antimicrosomal antibodies, although further statistical analysis, taking into account the serum TSH concentration, did not identify patients' antibody status as an independent risk predictor. Previous studies have found the presence of antithyroglobulin and antithyroid peroxidase antibodies not to be useful in distinguishing benign from malignant lesions (33).…”
Section: Discussionmentioning
confidence: 93%
“…In humans, serum Tg levels may be increased in all thyroid disease (with the exception of athyroidism and Tg synthesis defects) (10)(11)(12)(13). Particularly in thyroid cancer very high levels can be found (14)(15)(16)(17)(18). However, in man, there is a great overlap be¬ tween Tg levels in normal individuals and cancer patients (19), as well as between cancer patients and patients with other thyroid illnesses (13,20).…”
mentioning
confidence: 99%